2016
DOI: 10.1159/000443881
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Small for Gestational Age: Accuracy of Different Sonographic Fetal Weight Estimation Formulas

Abstract: Objective: To compare the accuracy of various sonographic estimated fetal weight (sEFW) formulas for the prediction of small for gestational age (SGA) neonates. Methods: A retrospective analysis of 6,126 fetal biometrical measurements performed within 3 days of delivery. SGA prediction was evaluated for various sEFW formulas by calculating the sensitivity, specificity, positive/negative predictive value (PPV/NPV), likelihood ratio (+LR/-LR), overall accuracy and area under the receiver operating characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…In general, previous studies assessing the accuracy of different models for EFW in the prediction of birth weight have reached the conclusion that either the most, or among the most, accurate models were those reported by Hadlock et al . in all pregnancies, including those with a small or large baby.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, previous studies assessing the accuracy of different models for EFW in the prediction of birth weight have reached the conclusion that either the most, or among the most, accurate models were those reported by Hadlock et al . in all pregnancies, including those with a small or large baby.…”
Section: Discussionmentioning
confidence: 91%
“…Studies describing new models have often reported that their model was superior to previously published ones, but this is an inevitable consequence of deriving and testing a model in the same population. In general, previous studies assessing the accuracy of different models for EFW in the prediction of birth weight have reached the conclusion that either the most, or among the most, accurate models were those reported by Hadlock et al 15 in all pregnancies, including those with a small or large baby [50][51][52][53][54][55][56][57] .…”
Section: Comparison With Previous Studiesmentioning
confidence: 92%
“…This finding is consistent with the pathophysiology of the development of placental insufficiency that mostly occurs in the third trimester, thus a previous growth scan could not possibly predict SGA at term. A recent study by Gabbay-Benziv et al [25] on a large cohort of nonlaboring women demonstrated that the formula of Hadlock et al [14] combining FL, AC, and HC performed best for the detection of SGA. In the current study, the Hadlock formula that performed best for SGA detection combined FL, BPD, AC, and HC.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic and random error in these methods is estimated to be from ‐8.7 to 16.1% and from 7.2 to 10.5% in a recent evaluation (Gabbay‐Benziv et al, ), with the most accurate method confirmed to be Hadlock's formula (Hadlock et al, ), which calculates estimated fetal weight from three biometric measurements: head and abdominal circumference and femoral length. These limitations are even more apparent when cardiac output is estimated in complex situations such as in an SCT that may be the size of the fetus.…”
Section: Discussionmentioning
confidence: 99%